Value Chain Analysis of Island Mackerel (Rastrelliger faughni) in Selected Coastal Municipalities in Lagonoy Gulf, Philippines - Mary Matthew N. Jamer; Maria Teresa J. Manzano (Jurnal Manajemen dan Agribisnis, 2025)
Background: Fisheries play a crucial role in food security and livelihoods in coastal communities. However, inefficient value chains hinder optimal economic returns for small-scale fishers. Analyzing the value chain of island mackerel (Rastrelliger faughni) in the Lagonoy Gulf helps to identify bottlenecks and areas for improvement.Purpose: This study aimed to assess the value chain of island mackerel in selected coastal municipalities around the Lagonoy Gulf, Philippines, to understand its structure, dynamics, and socioeconomic implications.Design/methodology/approach: This study employed a case study approach using primary data (surveys, interviews, focus groups with fishers, traders, and local officials) and secondary data. It involved a total of 114 respondents, including 100 fisherfolks representing the target population, 10 participants in focused group discussions (FGDs), and four key informant interviews (KIIs) with fishery experts selected from the local government and barangay officials, including a municipal agriculturist, an agriculture technologist in the fisheries sector, and a Department of Agriculture officer. The value chain analysis framework was used to map the actors, flows, and margins.Findings/Results: The study revealed key actors, such as fishers, consolidators, retailers, and processors. Price disparity and limited infrastructure were identified as major constraints. The value chain analysis showed that fishermen earned the highest average net profit, earning 95.30% during the peak season and 59.65% during the lean season. Retailers earned 15.19% during peak and 9.11% in lean seasons, whereas processors’ profit margins varied by product, with seasoned dried buraws reaching up to 57.91% in the peak season and 63.02% in the lean season. Retailer processors showed strong profitability, with margins of 82.84% (peak) and 77.33% (lean).  Recommendations include strengthening fisher cooperatives, improving cold-storage access, and enhancing market linkages. Conclusion: The value chain of island mackerel in the Gulf of Lagonoy has the potential for economic improvement. However, inefficiencies and limited support hinder performance. A more coordinated approach among stakeholders can significantly enhance the outcomes.Originality/value (state-of-the-art): This study provides a comprehensive local-scale value chain analysis of island mackerels in the Philippines. This study provides practical insights for fishery development, particularly in coastal community contexts. Keywords: island mackerel, value chain, fisheries, coastal municipalities, Lagonoy Gulf